Pengaruh Faktor Ketidakpastian Terhadap Contingency Cost Kontraktor di Provinsi Aceh - Sarrun (LPPM Universitas Almuslim, 2023)
The estimated cost of construction is done before physical implementation of the construction is done and requires a detailed analysis and compilation of the document because the estimated cost of having an impact on the success of the project and the company. Therefore, the contractor needs to allocate a number of contingency cost in every bid submitted in order to anticipate any uncertainty that may occur. In this study, the research object is the contractor companies that have classified the building and qualification of small, medium, and large based on the classification of qualifications according to Regulation Contractors National Construction Services Development Board No. 5 of 2014 on Integrated Construction Services Business Registration, where the number of respondents in This research was 37 respondents. The data used in this study in the form of interviews and questionnaires filled out by the contractor. Data processing is done by validity, reliability analysis, mean analysis, analysis Frequency Index (FI), the analysis Severity Index (SI) and analysis of Importance Index (II). The result is expected to be useful for the development of research in the field of Construction Management and can be in the form of reference information for the perpetrators of construction services in making estimates of indirect costs on construction projects in an effort to improve the cost-effectiveness at the same price competitive bidding. At the end of this study are expected to be able to contribute useful information for subsequent research. Results from this study showed that 5 (five) top factors into the factors contributing to the uncertainty affecting the implementation of the contingency cost building construction projects, namely loss (theft) within the project, cost estimation errors, the method used is less precise execution, delays in procurement of materials and equipment, and lack of control over the implementation of the technology. These five factors are divided into two categories the dominant cause of uncertainty that influence the conduct of contingency cost building construction projects based on answers from the three groups of respondents, namely the financial condition of the team, safety and security at the project site, and the managerial capabilities of the teams involved.